Solid-phase extraction as promising sample preparation method for compound of emerging concerns analysis - Dušan Rakić; Igor Antić; Jelena Živančev; Maja Buljovčić; Zita Šereš; Nataša Đurišić-Mladenović (Analecta, 2023)
Today’s environment is under the influence of numerous substances and most of them are not covered by current national and international regulations. Substances that are classified as contaminants of emerging concern, CECs, are not regulated nor systematically controlled in the environment, and they belong to the different chemical classes such as pesticides in current use, pharmaceutically active compounds (PhACs), personal care products, illicit drugs, hormones, micro- and nano-plastics, per- and poly-fluoroalkyl substances (PFAS), and many others. Once released CECs end up in surface water where they can be either accumulated or transported to the other environmental compartments, i.e. soil (by irrigation), underground water, or drinking water. The aim of the research was to investigate the efficiency of different selected solid-phase extraction (SPE) cartridges for preparation of water samples for simultaneous analysis of several CECs. For this purpose, a model mix solution of selected CECs in concentration relevant to environmental appearance was used. The selected CECs (14 PhACs, 11 pesticides in current use, and 4 PFAS) represented emerging contaminants with different properties, including polarities, and varying adverse effect on the environment and human health. Different types of sorbents were investigated: (i) commercial single-layer HLB, (ii) homemade multi-layer I: HLB plus a mix of WAX, WCX, and PPL, and (iii) multi-layer II: mix of WAX, WCX, and PPL plus HLB. The results revealed that the single-layer sorbent showed better efficiency in extraction of the analyzed CECs. Multi-layer sorbent should be further investigated to elucidate the possible reason for the poor extraction of some compounds, as development of a balanced extraction for a wider range of contaminants with different polarities, especially for non-target analysis of chemical residues, is required in order to capture the occurrence of the full profile of micropollutants.